Sistem Informasi Akuntansi Pegawai (KOSIPA ) PT ENVICON EKATAMA - Komalasari, Yuli; Laetussaadah, Lela; Mustomi, Dede; Alfianti, Zulia Imami (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2022)
Koperasi Pegawai was established to facilitate employees in managing employee funds that are stored and loaned for employees at PT. Envicon Ekatama. Guaranteed service for Koperasi participants needs to be made and designed systems that can support existing businesses.. The computer system at the Koperasi PT. Envicon Ekatama has not been used in its administration such as data input, savings,loan and installment data, as well as reporting requirements. In this study, the Employee Cooperative Information System (KOSIPA) with SQL programming language has been implemented, starting with analyzing the existing system, analyzing needs, creating and designing systems and software and hardware specifications, so that the system can run as expected.